(untitled) (Revista Română de filosofie analitică, 2025)
The occurrence of social comprehension difficulties when people living with autism, henceforth: autistics,2 interact with neurotypicals motivates the re-emergence of key questions about the mind and its interaction with other minds; what are minds and how do they relate to the world and others? The disruption of smooth social interaction brings forth the question of how is a mind able to socially interact and this question motivates one to tacitly provide a definition of what a mind is. This is visible in Simon-Baron Cohen’s exposition of the theory of mind theory, henceforth: ToM, in his book Mindblindness. In this book, Baron Cohen states that autistics have at least a degree of mindblindess and that mindreading3 is the means through which the mind relates to other minds.4 His tacit descriptions of ontological properties of the mind, henceforth: ontological descriptions or assertions, are utterly different from those provided by enactivists and by those who contribute to the 20th century tradition of phenomenology, henceforth: phenomenologists.5 The tension between the ontological descriptions of ToM Theory and those provided by enactivists and phenomenologists has led to a thriving battle ground. This article’s key aim is to provide descriptions that facilitate enactivist or phenomenological analyses that engage with the double empathy problem hypothesis. To bring its aim to fruition, I follow three steps. Firstly, I define the approaches and concepts I use: phenomenology, enactivism, and the double empathy problem. Secondly, I argue in favor of using phenomenology and enactivism for explaining social difficulties in autism by presenting two, at least prima facie, disadvantages of Baron Cohen’s articulation of ToM theory; one disadvantage stems from the ethical implications of his ontological assertions and the other stems from his ontological assertions. Thirdly, I describe autistic-neurotypical social interactions in a non-pathologizing manner by performing an enactivist analysis of the double-empathy problem surrounding autistic-neurotypical social interactions.